Better Together: A Model for Women and LGBTQ Equality in the Workplace - García Johnson, Carolina Pía; Otto, Kathleen (Frontiers in Psychology, 2019)
Much has been achieved in terms of human rights for women and people of the lesbian, gay, bisexual, transsexual, and queer (LGBTQ) community. However, human resources management (HRM) initiatives for gender equality in the workplace focus almost exclusively on white, heterosexual, cisgender women, leaving the problems of other gender and social minorities out of the analysis. This article develops an integrative model of gender equality in the workplace for HRM academics and practitioners. First, it analyzes relevant antecedents and consequences of gender-based discrimination and harassment (GBDH) in the workplace. Second, it incorporates the feminist, queer, and intersectional perspectives in the analysis. Third, it integrates literature findings about women and the LGBTQ at work, making the case for an inclusive HRM. The authors underscore the importance of industry-university collaboration and offer a starters’ toolkit that includes suggestions for diagnosis, intervention, and applied research on GBDH. Finally, avenues for future research are identified to explore gendered practices that hinder the career development of women and the LGBTQ in the workplace.